Application Status and Efficiency Improvement Path of AI-Assisted Tools in the UI Design Process - Cai, Hao (European Journal of AI, Computing & Informatics, 2025)
Over the past decade, user interface (UI) design has become increasingly complex due to multi-platform ecosystems and diversified interaction channels. In response, AI-assisted tools-leveraging large language models, generative image models, and predictive interaction analytics-have begun transforming the UI design process by automating wireframe generation, visual variation exploration, layout optimization, and prototype code production. This review systematically examines the current application status of AI in UI design, highlighting measurable efficiency gains in time savings, design quality, and cross-functional collaboration. It also identifies persistent challenges, including creative limitations, model reliability, data privacy, and shifting designer roles. Finally, the paper proposes a structured efficiency improvement path, integrating technical, organizational, and ethical considerations, aiming to guide the responsible and effective deployment of AI in modern UI design workflows.